Hypoxia and transforming growth factor β1 regulation of long non‐coding RNA transcriptomes in human pulmonary fibroblasts. Issue 1 (10th January 2020) - Senavirathna, Lakmini K.; Huang, Chaoqun; Pushparaj, Samuel; Xu, Dao; Liu, Lin
Abstract: One of the key characteristics of idiopathic pulmonary fibrosis (IPF) is accumulation of excess fibrous tissue in the lung, which leads to hypoxic conditions. Transforming growth factor (TGF) β is a major mediator that promotes the differentiation of fibroblasts to myofibroblasts. However, how hypoxia and TGFβ together contribute the pathogenesis of IPF is poorly understood. Long non‐coding RNAs (lncRNAs) have regulatory effects on certain genes and are involved in many diseases. In this study, we determined the effects of hypoxia and/or TGFβ on mRNA and lncRNA transcriptomes in pulmonary fibroblasts. Hypoxia and TGFβ1 synergistically increased myofibroblast marker expression. RNA sequencing revealed that hypoxia and TGFβ1 treatment resulted in significant changes in 669 lncRNAs and 2, 676 mRNAs compared to 150 lncRNAs and 858 mRNAs in TGFβ1 alone group and 222 lncRNAs and 785 mRNAs in hypoxia alone group. TGFβ1 induced the protein expression of HIF‐1α, but not HIF‐2α. On the other hand, hypoxia enhanced the TGFβ1‐induced phosphorylation of Smad3, suggesting a cross‐talk between these two signaling pathways. In all, 10 selected lncRNAs (five‐up and five‐down) in RNA sequencing data were validated using real‐time PCR. Two lncRNAs were primarily located in cytoplasm, three in nuclei and five in both nuclei and cytoplasm. The silencing of HIF‐1α and Smad3, but not Smad2 and HIF‐2α rescued the downregulation of FENDRR by hypoxia and TGFβ1. In conclusion, hypoxia and TGFβ1 synergistically regulate mRNAs and lncRNAs involved in several cellular processes, which may contribute to the pathogenesis of IPF. Abstract : One of the key characteristics of Idiopathic pulmonary fibrosis (IPF) is accumulation of excess fibrous tissue in the lung, which leads to hypoxic conditions. Transforming growth factor (TGF) β is a major mediator that promotes the differentiation of fibroblasts to myofibroblasts. Hypoxia and TGFβ1 synergistically regulate mRNAs and lncRNAs involved in several cellular processes, which may contribute to the pathogenesis of IPF.